PENGEMBANGAN SENSOR KIMIA UNTUK MONITORING PENGAWET BENZOAT DI DALAM BERBAGAI JENIS MI NUMAN - Sinaga, Marudut; Simanungkalit, Betaria; Situmorang, Manihar (JURNAL PENELITIAN SAINTIKA, 2013)
The development of chemical sensor for monitoring of food preservatives of bezoic acid in various types of beverages is explained. Thesensor was developed by the integration of spectrometric cell, UV detectorin UV-Vis spectrometric system. The sensor signal is obtained from themeasurement of bozoic acidic at il 229.65 nm. The chemical sensor give sensitive response to benzoic acid, where the detection linierity is liesbeween 0.05 - 40 ppm benzoic acid, slope slop 0.0613 au/ppm benzoicacid, and the detection limit is 0.01 ppm benzoic acid. The chemical sensorhas been applied for the determination of bezoic acid in real sample, wherethe concentration of benzoic acid in the bevereges are found in the range of 7 - 700 ppm benzoic acid. The measurements obtained with chemicalsensor are agree with that HPLC standard method (R2 = 0.932) ..